No matter what - Gliori, Debi (London : Bloomsbury Publishing, 2015)
Small, a little fox, seeks reassurance that Large will always provide love, no matter what.
Primary
Keywords: Parent and child -- Fiction; Love -- Fiction; Foxes -- Fiction